A new highly apomorphic species of Bujurquina (Teleostei: Cichlidae) from a reverse flowing river in the Peruvian Amazon, with a key to the species in the genus - Říčan, Oldřich; Říčanová, Štěpánka (European Journal of Taxonomy, 2023)
Bujurquina is the most widely distributed and species-rich genus of cichlids in the western Amazon of South America. In this study we describe a new species from Peru from a hypothesized reverse flowing river system. Prior to the origin of the modern Amazon River at 4.5 Ma, this river system had its headwaters on the Iquitos arch, one of several main structural arches (swells) in the Amazon. Prior to the origin of the modern Amazon these arches formed topographic barriers of drainage basins in lowland Amazonia. For our analyses we use morphological and molecular data, analyzed through multivariate statistics and molecular phylogenies, respectivelly. For all valid species in the genus (except B. cordemadi and B. pardus) we additionally for the first time provide photographs of live specimens. Based on DNA phylogeny and coloration patterns we demonstrate that Bujurquina is divided into two main clades and based on this we provide a dichotomous key for all the species.